Bioprospecção e purificação de substâncias bioativas produzidas por Streptomyces tubercidicus, endofítico isolado de Solanum lycocarpum St. Hill (Lobeira) do cerrado de São Carlos-SP - Ratti, Regiane Priscila (Universidade Federal de São Carlos, 2009)
The need for new and useful compounds to provide assistance and relief in all aspects of human condition is ever-growing. Drug resistance in bacteria, the appearance of life-threatening viruses, and the increase in the incidence of fungal infections in the world s population all underscore our inadequacy to cope with these medical problems. Endophytic microorganisms that colonize internal tissues of plants without causing any negative effects are relatively unstudied as potential sources of novel natural products for medical and commercial exploitation. The Streptomycetes provide nearly 80% of all the world s antibiotics produced. The aim of this work was to investigate the Brazilian tropical savannah tree Solanum lycocarpum St. Hill (Lobeira) in São Carlos, in order to isolate the endophytic microorganisms associated with the plant, separating and purifying the bioactives substances produced by the endophytic microorganism. The bioactivity of S. tubercidicus against pathogenic microorganisms was analyzed. The obtained results point out the antagonistic potential of the endophytic isolated against microorganisms of interest in Public Health. The brute extract fresh produced by S. tubercidicus RND-C it presented antimicrobial potential maximum of 200 UA.mL-1 against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923 after 48 h of cultivation; The bioactive substances produced by S. tubercidicus were submitted to different thermal and enzymatic treatments and pH variation to be determined the nature of the bioactive compounds. After it being submitted to enzymatic treatment with amylase and pepsin, the concentrated extract stayed bioactive, suggesting the lipidic and no-prothein nature of the bioactive substances. Already the active compounds against E. coli suggests the presence of a substance of glycidic and lipidic nature, due to resistance to the action of the enzyme invertase and lipase, respectively, suggesting that the substances contained in the brute extract of S. tubercidicus RND-C against E.coli can be a ´glycolipid. The concentrated extract stayed active biologically when exposed to lower (-20 and -80 ºC) and high (100 and 121 ºC) temperatures, suggesting that the bioactive compounds produced are not subject to spontaneous degradation. The extract stayed active against E. coli in acidity conditions (pH, 2,0 - 5,0) and it also presented bioactivity in pH 7,0 and 8,0. In conditions of high alkalinity (pH 9,0) bioactivity was not detected. Already against S. aureus, the extract stayed assets in the strip of pH 7,0. In conditions of acidity and alkalinity the bioactive substances produced by S. tubercidicus were inactivated. The molar mass of the substances was esteemed in minor than 3,0KDa. The bioactive molecules contained in the concentrated extract produced by S. tubercidicus RNC-C were purified and separated by bio monitoring analyzes, suggesting the presence of two different substances. The evaluation of the separation using a hight performance liquid chromatography (HPLC), suggests the existence of two different substances produced by S. tubercidicus, one being active against S. aureus and the other one active against E.coli and S. aureus. In the separation by using reverse-phase chromatography (Sep-Pak), were obtained four fractions (St. 1, St. 2, St. 3 and St. 4). The fractions St. 2 and St. 4 presented antimicrobial activity against bacteria and they were purified separately by Sephadex LH-20 Gel permeation chromatography obtaining the fractions St. 2-A; St. 2- B; St. 4-A and St. 4-B. The fractions St. 2-B was activity against S. aureus. Already the fractions St. 4-B was activity against S. aureus and E. coli. These results suggest the presence of two different substances. This work intends to contribute for understanding the interactions of endophitic and plants besides opening new perspectives on the biotechnological potential of the endophitics microorganisms of plants. The investigation of new composed assets biologically starting from microorganisms brings important contributions for the discovery of new drugs.
Bioprospection and purification of bioactives substances produced by Streptomyces tubercidicus, endophytic isolated of Solanum lycocarpum St. Hill (Lobeira) the Brazilian tropical savannah of São Carlos-SP
Keywords: Microbiologia industrial; Streptomyces; Microrganismos endofíticos; Antibióticos; Cerrados; Purificação; OUTROS